تأثير الميزانية الصوتية على التكفل الصوتي - عكرون, سامية (جامعة الوادي - University of Eloued, 2020)
البحة الصوتية ليس بالأمر الهين، ولكن المجتمع الجزائري لا يعطون أهمية لهذا الاضطراب، نجد أفراد يعانون من اضطراب صوتي أكثر سنتين أو ثلاث بدون أن يستشيروا مختص كأن الأمر لا يهمهم بتاتا. خلال تقربنا للمراكز الإستشفائية، لاحظنا نقائص كثيرة وفادحة صدرت من طرف المختصين الأرطفونين (ميزانية ناقصة، تشخيص الأرطفوني وتسجيل صوت المفحوص منعدمة....إلخ) لذا إقتراحنا ميزانية كاملة حتى توفي بالغرض لأنها ستسمح للمختص أن يجمع كم هائل من المعلومات الخاصة بالمفحوص، أن يقيم صوت المفحوص تقيما ذاتيا بواسطة سلم وتقييما موضوعيا بواسطة برمجية كما يذكره بوصف السلوك الصوتي.Abstract: Dysphonia is not a common disorder, but the Algerian Society does not consider it as a disorder, because there are many dysphonics whose disorder goes back two or three years, without consulting a specialist. During our investigations in hospital settings, we have noted many weaknesses that this is in: the incomplete history, the recording of the patient’s voice does not exist, the diagnosis of the speech therapist does not establish. For these reasons, we have proposed a complete vocal check-up so that the speech therapist can meet all the patient’s expectations, namely: - Gathers a large amount of information about the patient; - A subjective evaluation using the GRBAS scale; - An objective evaluation with PRAAT software; - An analysis of the gesture.
بالمصابين بالبحة الصوتية
مقال
Keywords: الإضطراب الصوتي ; الميزانية الصوتية ; التقييم الذاتي ; التقييم الموضوعي ; السلوك الصوتي; dysphony ; vocal balance ; subjective evaluation GRBAS ;objective evaluation ; PRAAT; vocal gestur